Fathers' constructions of the spatial worlds of boyhood in Ottawa: Geographies of memory and masculinity - Mannella, Matthew (University of Ottawa (Canada), 2008)
This study's objective was to uncover the role of fathers in constructing the spatial boundaries of their sons' childhoods and providing them access to play spaces, as informed by the fathers' memories of their own childhoods. In order to understand the meanings that fathers attribute to their experiences with boyhood worlds, ten semi-structured interviews were completed with fathers living in Ottawa. The fathers expressed uneasiness with what they perceive to be an increasing level of structure in their sons' play spaces. While most of the fathers attributed this decrease in autonomy to safety concerns for their sons, some fathers noted that organized play is in opposition with their experiential knowledge of boyhood in terms of risk and adventure. The study emphasizes the different ways in which fathers navigate through both societal expectations of good parenting and their understanding of masculinity as they create spatial worlds of boyhood for their sons.
Keywords: Geography.; Sociology, Individual and Family Studies.